Effect of Gamma-Irradiation on Tocopherols and Free Fatty Acids in Walnut and Almond - Jubeen, Farhat; A. Bhatti, Ijaz; Nawaz Bhatti, Haq; Ahmad Sheikh, Munir (Asian Journal of Chemistry, 2012)
The present study was aimed to investigate the effect of storage period and g irradiation on tocopherols and free fatty acids composition in walnut and almond. Samples of nuts were randomly selected from the retail outlets of Faisalabad, Pakistan. The moisture content of the nuts was increased to 10 ± 3 and 16 ± 3 %. The stored nut samples were exposed to 0, 2, 4, 6 and 8 kGy g radiation absorbed doses after a storage period of 12 weeks. The decrease in individual and total tocopherols of unirradiated nuts was significant during a storage period of 12 weeks and non significant in irradiated nuts. There was a significant increase in saturated fatty acids with a considerable decrease in unsaturated fatty acids during storage. In irradiated nuts, there was an increase in saturated fatty acids, considerable decrease in monounsaturated fatty acid and polyunsaturated fatty acids remained unchanged.